Implementasi Hukuman Pendidikan dalam Penerapan Disiplin di Pondok Insan Mulia Maburai - Musayyifi, Khalif; Madrah, Muna Yastuti (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2022)
This paper discusses how the implementation of educational punishment in applying discipline at the Insan Mulia Mandiri Islamic Boarding School. Various problems occur in educational institutions, especially in Islamic boarding schools due to corporal punishment in enforcing discipline which can result in revenge when they become seniors or administrators of the Islamic boarding school. The application of discipline in Islamic boarding schools is very important because Islamic boarding schools are a means in the process of forming and fostering the morals of students and developing the self-potential of students with the aim of creating superior generations with good morals, intellect, and trustworthiness. This study uses a type of field research that is qualitative. Data collection was carried out by observation, interview and documentation techniques. Sources of data in this study were 2 administrators for caring for students and 3 students. The results showed that the implementation of educational punishment at the Insan Mulia Mandiri Islamic Boarding School was divided into 3 levels. Minor disciplinary violations, moderate disciplinary violations, and serious disciplinary violations. Punishments given to students according to the violations committed. After the educational punishment was applied, the students were more active and obedient to the existing discipline. Although there are obstacles faced, namely within 2 weeks there are students who violate the rules. Meanwhile, students who receive education punishment do not hold grudges, can even increase their knowledge, read the Al-Qur'an more fluently, get more Al-Qur'an memorization, can know how to farm and raise fish. So the implementation of this educational punishment is very effective in implementing the discipline of the students of the Insan Mulia Mandiri Islamic Boarding School